Homogenization on multi-materials' elements: application to printed circuit boards and warpage analysis - Araújo, Manuel (2016)
Multi-material domains are often found in industrial applications. Modelling them can be computationally very expensive due to meshing requirements. The finite element properties comprising different materials are hardly accurate. In this work, a new homogenization method that simplifies the computation of the homogenized Young modulus, Poisson ratio and thermal expansion coefficient is proposed, and applied to composite-like material on a printed circuit board. The results show a good properties correspondence between the homogenized domain and the real geometry simulation.